Developing a deep canonical correlation-based technique for seizure prediction - Vieluf, Solveig; Hasija, Tanuj; Kuschel, Maurice; Reinsberger, Claus; Loddenkemper, Tobias (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

An interval multi-criteria decision-making model for evaluating blockchain-IoT technology in supply chain networks - Tavana, Madjid; Khalili Nasr, Arash; Ahmadabadi, Alireza Barati; Amiri, Alireza Shamekhi; Mina, Hassan (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Analytic hierarchy process and data envelopment analysis: A match made in heaven - Tavana, Madjid; Soltanifar, Mehdi; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

A Discrete and Continuous Study of the Max-Chain-Formation Problem - Castenow, Jannik; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Information and Computation)
Keywords: Computational Theory and Mathematics; Computer Science Applications; Information Systems; Theoretical Computer Science

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate - Hanke, Marcel; Hansen, Niklas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation time. Using DNA origami nanostructures as sensors that translate small molecular transitions into nanostructural changes, the denaturing effects of the Gdm salts were directly visualized by atomic force microscopy. GdmSCN was the most potent DNA denaturant, which caused complete DNA origami denaturation at 50 °C already at a concentration of 2 M. Under such harsh conditions, denaturation occurred within the first 15 min of Gdm exposure, whereas much slower kinetics were observed for the more weakly denaturing salt Gdm2SO4 at 25 °C. Lastly, we observed a novel non-monotonous temperature dependence of DNA origami denaturation in Gdm2SO4 with the fraction of intact nanostructures having an intermediate minimum at about 40 °C. Our results, thus, provide further insights into the highly complex Gdm–DNA interaction and underscore the importance of the counteranion species.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Joining of CFRT/Steel Hybrid Parts via Direct Pressing of Cold Formed Non-Rotational Symmetric Pin Structures - Popp, Julian; Römisch, David; Merklein, Marion; Drummer, Dietmar (Applied Sciences)
In this study, quasi-unidirectional continuous fiber reinforced thermoplastics (CFRTs) are joined with metal sheets via cold formed cylindrical, elliptical and polygonal pin structures which are directly pressed into the CFRT component after local infrared heating. In comparison to already available studies, the unique novelty is the use of non-rotational symmetric pin structures for the CFRT/metal hybrid joining. Thus, a variation in the fiber orientation in the CFRT component as well as a variation in the non-rotational symmetric pins’ orientation in relation to the sample orientation is conducted. The created samples are consequently mechanically tested via single lap shear experiments in a quasi-static state. Finally, the failure behavior of the single lap shear samples is investigated with the help of microscopic images and detailed photographs. In the single lap shear tests, it could be shown that non-rotational symmetric pin structures lead to an increase in maximum testing forces of up to 74% when compared to cylindrical pins. However, when normalized to the pin foot print related joint strength, only one polygonal pin variation showed increased joint strength in comparison to cylindrical pin structures. The investigation of the failure behavior showed two distinct failure modes. The first failure mode was failure of the CFRT component due to an exceedance of the maximum bearing strength of the pin-hole leading to significant damage in the CFRT component. The second failure mode was pin-deflection due to the applied testing load and a subsequent pin extraction from the CFRT component resulting in significantly less visible damage in the CFRT component. Generally, CFRT failure is more likely with a fiber orientation of 0° in relation to the load direction while pin extraction typically occurs with a fiber orientation of 90°. It is assumed that for future investigations, pin structures with an undercutting shape that creates an interlocking joint could counteract the tendency for pin-extraction and consequently lead to increased maximum joint strengths.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Mincut Sensitivity Data Structures for the Insertion of an Edge - Baswana, Surender; Gupta, Shiv; Knollmann, Till (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Anion-specific structure and stability of guanidinium-bound DNA origami - Hanke, Marcel; Dornbusch, Daniel; Hadlich, Christoph; Rossberg, Andre; Hansen, Niklas; Grundmeier, Guido; Tsushima, Satoru; Keller, Adrian; Fahmy, Karim (Computational and Structural Biotechnology Journal)
Keywords: Computer Science Applications; Genetics; Biochemistry; Structural Biology; Biophysics; Biotechnology

Robust estimation of clinch joint characteristics based on data-driven methods - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (The International Journal of Advanced Manufacturing Technology)
Given a steadily increasing demand on multi-material lightweight designs, fast and cost-efficient production technologies, such as the mechanical joining process clinching, are becoming more and more relevant for series production. Since the application of such joining techniques often base on the ability to reach similar or even better joint loading capacities compared to established joining processes (e.g., spot welding), few contributions investigated the systematic improvement of clinch joint characteristics. In this regard, the use of data-driven methods in combination with optimization algorithms showed already high potentials for the analysis of individual joints and the definition of optimal tool configurations. However, the often missing consideration of uncertainties, such as varying material properties, and the related calculation of their impact on clinch joint properties can lead to poor estimation results and thus to a decreased reliability of the entire joint connection. This can cause major challenges, especially for the design and dimensioning of safety-relevant components, such as in car bodies. Motivated by this, the presented contribution introduces a novel method for the robust estimation of clinch joint characteristics including uncertainties of varying and versatile process chains in mechanical joining. Therefore, the utilization of Gaussian process regression models is demonstrated and evaluated regarding the ability to achieve sufficient prediction qualities.
Keywords: Industrial and Manufacturing Engineering; Computer Science Applications; Mechanical Engineering; Software; Control and Systems Engineering

Seizing the Opportunity for Automation—How Traffic Density Determines Truck Drivers' Use of Cruise Control - Hoffmann, Christin; Thommes, Kirsten (IEEE Transactions on Human-Machine Systems)
Keywords: Artificial Intelligence; Computer Networks and Communications; Computer Science Applications; Human-Computer Interaction; Signal Processing; Control and Systems Engineering; Human Factors and Ergonomics

Learning to Plan by Learning to Reflect?—Exploring Relations between Professional Knowledge, Reflection Skills, and Planning Skills of Preservice Physics Teachers in a One-Semester Field Experience - Vogelsang, Christoph; Kulgemeyer, Christoph; Riese, Josef (Education Sciences)
Following concepts describing lesson planning as a form of anticipatory reflection, preservice physics teachers’ reflection skills are assumed to be positively connected with their planning skills. However, empirical evidence on this is scarce. To explore how relations between these specific skills change over the course of a field experience controlling for influences of professional knowledge, we conduct a pre-post field study with N = 95 preservice physics teachers in a one-semester field experience. Content knowledge (CK) and pedagogical content knowledge (PCK) (paper-and-pencil tests), and reflection and planning skills (standardized performance assessments) were assessed before and after the field experience. Path analyses revealed almost no influence of reflection skills on planning skills. Reflections skills did not contribute to preservice teachers planning skills beyond knowledge, indicating both constructs might represent rather independent abilities. The results show the need for further development of models describing the development of teachers’ professional knowledge and skills in academic teacher education and for the development of concepts for a better integration of reflection and lesson planning in field experiences.
Keywords: Public Administration; Developmental and Educational Psychology; Education; Computer Science Applications; Computer Science (miscellaneous); Physical Therapy; Sports Therapy and Rehabilitation

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
Abstract While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Applying XAI to an AI-based system for candidate management to mitigate bias and discrimination in hiring - Hofeditz, Lennart; Clausen, Sünje; Rieß, Alexander; Mirbabaie, Milad; Stieglitz, Stefan (Electronic Markets (ELMA))
Abstract Assuming that potential biases of Artificial Intelligence (AI)-based systems can be identified and controlled for (e.g., by providing high quality training data), employing such systems to augment human resource (HR)-decision makers in candidate selection provides an opportunity to make selection processes more objective. However, as the final hiring decision is likely to remain with humans, prevalent human biases could still cause discrimination. This work investigates the impact of an AI-based system’s candidate recommendations on humans’ hiring decisions and how this relation could be moderated by an Explainable AI (XAI) approach. We used a self-developed platform and conducted an online experiment with 194 participants. Our quantitative and qualitative findings suggest that the recommendations of an AI-based system can reduce discrimination against older and female candidates but appear to cause fewer selections of foreign-race candidates. Contrary to our expectations, the same XAI approach moderated these effects differently depending on the context.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Physics informed neural networks for continuum micromechanics - Henkes, Alexander; Wessels, Henning; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Social/dialogical roles of social robots in supporting children’s learning of language and literacy—A review and analysis of innovative roles - Rohlfing, Katharina; Altvater-Mackensen, Nicole; Caruana, Nathan; van den Berghe, Rianne; Bruno, Barbara; Tolksdorf, Nils Frederik; Hanulíková, Adriana (Frontiers in Robotics and AI)
One of the many purposes for which social robots are designed is education, and there have been many attempts to systematize their potential in this field. What these attempts have in common is the recognition that learning can be supported in a variety of ways because a learner can be engaged in different activities that foster learning. Up to now, three roles have been proposed when designing these activities for robots: as a teacher or tutor, a learning peer, or a novice. Current research proposes that deciding in favor of one role over another depends on the content or preferred pedagogical form. However, the design of activities changes not only the content of learning, but also the nature of a human–robot social relationship. This is particularly important in language acquisition, which has been recognized as a social endeavor. The following review aims to specify the differences in human–robot social relationships when children learn language through interacting with a social robot. After proposing categories for comparing these different relationships, we review established and more specific, innovative roles that a robot can play in language-learning scenarios. This follows Mead’s (1946) theoretical approach proposing that social roles are performed in interactive acts. These acts are crucial for learning, because not only can they shape the social environment of learning but also engage the learner to different degrees. We specify the degree of engagement by referring to Chi’s (2009) progression of learning activities that range from active, constructive, toward interactive with the latter fostering deeper learning. Taken together, this approach enables us to compare and evaluate different human–robot social relationships that arise when applying a robot in a particular social role.
Keywords: Artificial Intelligence; Computer Science Applications

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

NTFA-enabled goal-oriented adaptive space–time finite elements for micro-heterogeneous elastoplasticity problems - Ju, X.; Mahnken, Rolf; Xu, Y.; Liang, L. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

New low order Runge–Kutta schemes for asymptotically exact global error estimation of embedded methods without order reduction - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Proactive Management of Requirement Changes in the Development of Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Preuß, Daniel (Applied Sciences)
Requirement changes and cascading effects of change propagation are major sources of inefficiencies in product development and increase the risk of project failure. Proactive change management of requirement changes yields the potential to handle such changes efficiently. A systematic approach is required for proactive change management to assess and reduce the risk of a requirement change with appropriate effort in industrial application. Within the paper at hand, a novel method for Proactive Management of Requirement Changes (ProMaRC) is presented. It is developed in close collaboration with industry experts and evaluated based on workshops, pilot users’ feedback, three industrial case studies from the automotive industry and five development projects from research. To limit the application effort, an automated approach for dependency analysis based on the machine learning technique BERT and semi-automated assessment of change likelihood and impact using a modified PageRank algorithm is developed. Applying the method, the risks of requirement changes are assessed systematically and reduced by means of proactive change measures. Evaluation shows high performance of dependency analysis and confirms the applicability and usefulness of the method. This contribution opens up the research space of proactive risk management for requirement changes which is currently almost unexploited. It enables more efficient product development.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia A.; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Demand response scheduling using derivative-based dynamic surrogate models - Di Pretoro, Alessandro; Bruns, Bastian; Negny, Stéphane; Grünewald, Marcus; Riese, Julia (Computers & Chemical Engineering)
Keywords: Computer Science Applications; General Chemical Engineering

A novel Interval Type-2 Fuzzy best-worst method and combined compromise solution for evaluating eco-friendly packaging alternatives - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Bonyani, Abbas (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

Fast Hands-Off Control Using ADMM Real-Time Iterations - Schulze Darup, Moritz; Book, Gerrit; Quevedo, Daniel E.; Nagahara, Masaaki (IEEE Transactions on Automatic Control)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

On the Stability of Linear Dynamic Controllers With Integer Coefficients - Schluter, Nils; Darup, Moritz Schulze (IEEE Transactions on Automatic Control)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

The rise of artificial intelligence – understanding the AI identity threat at the workplace - Mirbabaie, Milad; Brünker, Felix; Möllmann Frick, Nicholas R. J.; Stieglitz, Stefan (Electronic Markets)
Abstract Artificial intelligence (AI) is being increasingly integrated into enterprises to foster collaboration within humanmachine teams and assist employees with work-related tasks. However, introducing AI may negatively impact employees’ identifications with their jobs as AI is expected to fundamentally change workplaces and professions, feeding into individuals’ fears of being replaced. To broaden the understanding of the AI identity threat, the findings of this study reveal three central predictors for AI identity threat in the workplace: changes to work, loss of status position, and AI identity predicting AI identity threat in the workplace. This study enriches information systems literature by extending our understanding of collaboration with AI in the workplace to drive future research in this field. Researchers and practitioners understand the implications of employees’ identity when collaborating with AI and comprehend which factors are relevant when introducing AI in the workplace.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Digitally Assessing Text Comprehension in Grades 3-4: Test Development and Validation - Seifert, Susanne; Paleczek, Lisa (Electronic Journal of e-Learning)
A prerequisite for child reading support at school is adequate assessment. Embedding (repeated) assessment into daily teaching routine is often challenging for teachers in terms of time and organization. The use of digital tools can help teachers in the assessment process (in preparation, evaluation, documentation, etc.). A digital assessment tool (Graz Reading Comprehension test: GraLeV), focusing on assessing reading comprehension skills in Grades 3 and 4 is currently being developed in Austria. This reading assessment covers reading comprehension at the word, sentence, and text level. Text level is assessed via two subtests (Subtest I: presentation of nonsense-stories and corresponding questions, and Subtest II: maze selection). The other levels consist of one subtest each. This paper focusses on the subtests at text level. More specifically, the paper reports the results of two studies. Study 1 describes the development phases and the first piloting of these two subtests (data collection: 10/2019-12/2019). Testing 273 students with preliminary versions of the subtests (Subtest I: 30 items, Subtest II: 60 items) produced information on (a) item difficulty, (b) item discriminatory power, and (c) time limits for future speed testing. Items not meeting the required quality criteria were excluded. The final version of Subtest I consists of 16 questions referring to eight different, short, nonsense-texts. Its testing time (without instructions) is three minutes. The final version of the Subtest II consists of 2 texts each with 15 maze selections (30 items) and testing time is 100 seconds. The internal consistency is found to be good for Subtest I (α=.87) and Subtest II (α=.78 to .80). Study 2 reports on testing for validity and retest-reliability (data collection: 09/2020-11/2020). Student scores in another reading comprehension test, together with teacher assessments of reading comprehension, were used to assess congruent validity. Divergent validity was assessed using teacher assessments of mathematical and socio-emotional skills. As expected, the correlations with the congruent measures were higher than those with the divergent measures. A subsample was tested twice with the GraLeV. Retest-reliability was acceptable for Subtest II. However, the scores obtained at time 2 were higher compared to those at time 1 in both subtests. This is probably the result of increased student familiarity with the digital device and the digital test environment at time 2. The results are discussed in the light of teachers’ needs for standardized digital assessments in order to facilitate the tailoring of student reading support.
Keywords: Computer Science Applications; Education

Is Reading Comprehension Taken for Granted? An Analysis of Austrian Textbooks in Fourth and Sixth Grade - Seifert, Susanne (Technology, Knowledge and Learning)
Abstract The range of teaching materials now available is becoming increasingly diverse. Despite this, however, the use and influence of textbooks in teaching still remains very high. When instructing reading comprehension, teachers often use textbooks as the basis for teaching in language lessons. Establishing a good match between textbooks and the skills to be acquired is therefore essential. In this paper, I investigate whether textbooks used in Austrian schools can adequately support the teaching of reading comprehension skills. Since reading comprehension is the basis for acquiring knowledge in all subjects, science textbooks are examined in addition to (German) language lesson textbooks. Thus, the content pages of four language textbooks and four science textbooks for fourth and sixth grade were analysed in terms of five different categories, i.e. general structural setup, learning goals, text types, text structures, and activities. The results reveal clear variations with respect to learning goals in language textbooks. For example, the extent to which reading comprehension is addressed ranges from 13.64 to 69.70%, depending on the book used. Although not addressed as a learning goal in the science textbooks, reading comprehension is often presupposed, especially in sixth grade. While the instruction of reading comprehension ought to entail coverage of reading strategies, this is often neglected, or only dealt with indirectly. Given the diversity of textbooks analysed, it seems all the more important to stress that teachers should: 1) clarify the goals and teaching strategies of a book before using it, 2) become aware of strategies that support the development of students' reading comprehension, and 3) use textbooks as a complementary (and not sole) tool to support reading comprehension in all subjects.
Keywords: Computer Science Applications; Human-Computer Interaction; Education; Mathematics (miscellaneous)

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, Phillipp; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Medical & Biological Engineering & Computing)
Advances in EEG filtering algorithms enable analysis of EEG recorded during motor tasks. Although methods such as artifact subspace reconstruction (ASR) can remove transient artifacts automatically, there is virtually no knowledge about how the vigor of bodily movements affects ASRs performance and optimal cut-off parameter selection process. We compared the ratios of removed and reconstructed EEG recorded during a cognitive task, single-leg stance, and fast walking using ASR with 10 cut-off parameters versus visual inspection. Furthermore, we used the repeatability and dipolarity of independent components to assess their quality and an automatic classification tool to assess the number of brain-related independent components. The cut-off parameter equivalent to the ratio of EEG removed in manual cleaning was strictest for the walking task. The quality index of independent components, calculated using RELICA, reached a maximum plateau for cut-off parameters of 10 and higher across all tasks while dipolarity was largely unaffected. The number of independent components within each task remained constant, regardless of the cut-off parameter used. Surprisingly, ASR performed better in motor tasks compared with non-movement tasks. The quality index seemed to be more sensitive to changes induced by ASR compared to dipolarity. There was no benefit of using cut-off parameters less than 10.
Keywords: Computer Science Applications; Biomedical Engineering

Christian Efing / Karl-Hubert Kiefer (Hg.): Sprachbezogene Curricula und Aufgaben in der beruflichen Bildung. Aktuelle Konzepte und Forschungsergebnisse - Prikoszovits, Matthias (Deutsch als Fremdsprache)
Keywords: Computer Science Applications; History; Education

Verschlüsselte Regelung in der Cloud – Stand der Technik und offene Probleme - Schulze Darup, Moritz (at - Automatisierungstechnik)
Zusammenfassung Zukünftige Regelungskonzepte werden verstärkt auf Cloud-Computing und verteiltes Rechnen setzen. In den resultierenden vernetzten Regelungssystemen werden sensible Daten über öffentliche Netzwerke kommuniziert und auf Plattformen Dritter verarbeitet. Verschlüsselte Regelungen zielen darauf ab, die Vertraulichkeit dieser Daten im gesamten Regelkreis zu sichern. Um dieses Ziel zu erreichen, werden klassische Regelungsalgorithmen so modifiziert, dass sie verschlüsselte Regeleingriffe basierend auf verschlüsselten Systemzuständen berechnen. Zum Einsatz kommen dabei homomorphe Verschlüsselungsverfahren, die einfache mathematische Operationen auf verschlüsselten Daten ermöglichen. Der Artikel erläutert die Implementierung verschlüsselter Regelungen anhand von drei wegweisenden Realisierungen in der Cloud.
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Depth camera based statistical shape fitting approach for the creation of an individualized lower body biomechanical model: validity and reliability - Taetz, Bertram; Teufl, Wolfgang; Weidmann, Alexander; Pietschmann, Juliane; Jöllenbeck, Thomas; Bleser, Gabriele (Computer Methods in Biomechanics and Biomedical Engineering)
Keywords: Computer Science Applications; Human-Computer Interaction; Biomedical Engineering; General Medicine; Bioengineering

Equivariant bifurcations in four-dimensional fixed point spaces - Lauterbach, Reiner; Schwenker, Sören (Dynamical Systems)
In this paper we continue the study of group representations which are counterexamples to the Ize conjecture. As in previous papers we find new infinite series of finite groups leading to such counterexamples. These new series are quite different from the previous ones, for example the group orders do not form an arithmetic progression. However, as before we find Lie groups which contain all these groups. This additional structure was observed, but not used in the previous studies of this problem. Here we also investigate the related bifurcations. To a large extent, these are closely related to the presence of mentioned compact Lie group containing the finite groups. This might give a tool to study the bifurcations related to all low dimensional counterexamples of the Ize conjecture. It also gives an indication of where we can expect to find examples where the bifurcation behaviour is different from what we have seen in the known examples.
Keywords: Computer Science Applications; General Mathematics

Argumentation Mining in User-Generated Web Discourse - Habernal, Ivan; Gurevych, Iryna (Computational Linguistics)
The goal of argumentation mining, an evolving research field in computational linguistics, is to design methods capable of analyzing people's argumentation. In this article, we go beyond the state of the art in several ways. (i) We deal with actual Web data and take up the challenges given by the variety of registers, multiple domains, and unrestricted noisy user-generated Web discourse. (ii) We bridge the gap between normative argumentation theories and argumentation phenomena encountered in actual data by adapting an argumentation model tested in an extensive annotation study. (iii) We create a new gold standard corpus (90k tokens in 340 documents) and experiment with several machine learning methods to identify argument components. We offer the data, source codes, and annotation guidelines to the community under free licenses. Our findings show that argumentation mining in user-generated Web discourse is a feasible but challenging task.
Keywords: Artificial Intelligence; Computer Science Applications; Linguistics and Language; Language and Linguistics

Characterization and Analysis of the Hysteresis in a ZnO Nanoparticle Thin-Film Transistor - Vidor, F. F.; Wirth, G.; Assion, F.; Wolff, K.; Hilleringmann, Ulrich (IEEE Transactions on Nanotechnology)
Keywords: Electrical and Electronic Engineering; Computer Science Applications

Elektromobilität — ein aktuelles Forschungsfeld insbesondere der Regelungstechnik - Kröger, Claus; Böcker, Joachim; Neiß, Konstantin (at - Automatisierungstechnik)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Active Damping of Drive Train Oscillations for an Electrically Driven Vehicle - Amann, Notker; Böcker, Joachim; Prenner, Franz (IEEE/ASME Transactions on Mechatronics)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Denesting by Bounded Degree Radicals - Blömer, J. (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Strength difference in compression and tension and pressure dependence of yielding in elasto-plasticity - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Finite element simulation for rock salt with dilatancy boundary coupled to fluid permeation - Mahnken, Rolf; Kohlmeier, M. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Implicit integration scheme and its consistent linearization for an elastoplastic-damage model with application to concrete - Mahnken, Rolf; Tikhomirov, D.; Stein, E. (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

A comprehensive study of a multiplicative elastoplasticity model coupled to damage including parameter identification - Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering

Parameter estimation for a viscoplastic damage model using a gradient‐based optimization algorithm - Mahnken, Rolf; Johansson, Magnus; Runesson, Kenneth (Engineering Computations)
In this work a gradient‐based optimization method is applied in order to determine material parameters for a viscoplastic model with dynamic yield surface coupled to damage as presented in 1997. To this end a sensitivity analysis consistent with the integration scheme presented previously is performed in a systematic manner, both for strain and stress controlled experiments. The algorithm is tested in two numerical examples: first, simulated data are used, in order to re‐obtain parameters for the case of damage under monotonic loading. In the second example material parameters are obtained based on experimental data for lcf‐testing of an austenetic stainless steel, thus showing a very good agreement with respect to hardening, rate and damage effects.
Keywords: Computational Theory and Mathematics; Computer Science Applications; General Engineering; Software

A unified approach for parameter identification of inelastic material models in the frame of the finite element method - Mahnken, Rolf; Stein, Erwin (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics